Legal Protection for Consumers Related to Skincare Products and Bodycare Overclaim - Putri, Ribsi Esa Vylonia (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
The rise of misleading marketing practices in the midst of the rapid cosmetics industry, which results in losses for consumers, both material and immaterial. This study aims to identify forms of legal protection for consumers who are victims of overclaims and evaluate the role of the Food and Drug Supervisory Agency in handling these cases, using an empirical legal research method, primary data is obtained through questionnaires from consumers, while secondary data is obtained from literature studies, then analyzed qualitatively-descriptively. The results of the study show that business actors are prohibited from advertising or promoting goods incorrectly or misleadingly, including through overclaim. Violation of this article violates the consumer's right to honest and correct information. However, overclaim practices still often occur due to low compliance of business actors and lack of effective supervision and enforcement. Food and Drug Supervisory Agencies have a crucial role in pre-market to post-market oversight and enforcement, but face challenges in broad market coverage and digital dynamics. It is hoped that this thesis can provide a comprehensive understanding of rights and obligations in the context of overclaim, increase consumer awareness, encourage compliance of business actors, and become an input for the government and the Food and Drug Supervisory Agency in formulating more protective policies and effective law enforcement mechanisms to create a responsible cosmetics market.